2020
DOI: 10.1111/tpj.15043
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of starch synthesis in maize endosperm by microRNAs and DNA methylation

Abstract: SUMMARYStarch synthesis is an essential feature of crop filling, but knowledge of the molecular mechanisms regulating the expression of starch synthesis genes (SSGs) is currently limited to transcription factors (TFs). Here, we obtained transcriptome, small RNAome, and DNA methylome data from maize (Zea mays) endosperms during multiple developmental stages and established a regulatory network atlas of starch synthesis. Transcriptome analysis showed a sharp transition at 9–10 days after pollination, when genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…Previous studies have shown that genes preferentially expressed in the rice endosperm, including SSRGs, usually show reduced expression because of methylation, indicating that methylation is also involved in the regulation of starch synthesis ( Zemach et al., 2010 ). Recently, similar overall methylation patterns were found in the SSRGs expressed in the maize endosperm ( Hu et al., 2021 ). In the developing maize endosperm, the coding regions of low-expression SSRGs are highly methylated, and expression levels of SBE1 and Su1 correlate significantly and negatively with predicted DNA methylation marks ( Hu et al., 2021 ).…”
Section: Regulatory Network Of Starch Synthesis In Cereal Endospermssupporting
confidence: 65%
See 2 more Smart Citations
“…Previous studies have shown that genes preferentially expressed in the rice endosperm, including SSRGs, usually show reduced expression because of methylation, indicating that methylation is also involved in the regulation of starch synthesis ( Zemach et al., 2010 ). Recently, similar overall methylation patterns were found in the SSRGs expressed in the maize endosperm ( Hu et al., 2021 ). In the developing maize endosperm, the coding regions of low-expression SSRGs are highly methylated, and expression levels of SBE1 and Su1 correlate significantly and negatively with predicted DNA methylation marks ( Hu et al., 2021 ).…”
Section: Regulatory Network Of Starch Synthesis In Cereal Endospermssupporting
confidence: 65%
“…Recently, similar overall methylation patterns were found in the SSRGs expressed in the maize endosperm ( Hu et al., 2021 ). In the developing maize endosperm, the coding regions of low-expression SSRGs are highly methylated, and expression levels of SBE1 and Su1 correlate significantly and negatively with predicted DNA methylation marks ( Hu et al., 2021 ). Thus, DNA methylation may act as a switch in the global regulation of starch biosynthesis.…”
Section: Regulatory Network Of Starch Synthesis In Cereal Endospermssupporting
confidence: 65%
See 1 more Smart Citation
“…Similar cases were reported by previous studies [ 35 ]. For example, ZmMYB138 and ZmMYB115 for ZmmiR159k regulated the endosperm development of corn seeds by affecting the transcriptional activities of Du1/Wx and Ae1/Bt2 genes [ 36 ]. MYB89 was expressed predominantly in developing seeds during maturation, which inhibited seed oil accumulation by directly repressing WRI1 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limited set of transcription factors have been identified to date [ 106 ] that contribute to the regulation of storage starch synthesis mainly in Oryza sativa [ 107 , 108 ], Triticum aestivum [ 109 ], and Zea mays [ 110 , 111 , 112 ]. NAM, ATAF1/2, and CUC2 (NAC) are the major families of plant-specific transcription factors (TFs) [ 111 , 113 , 114 ], which are reportedly involved directly (physical binding) or indirectly (functional interaction attributed to other binding partners) in the regulation of starch biosynthesis through modulating the starch biosynthetic enzymes [ 115 ]. Based on previously reported work on Zea mays , ZmEREB156 was found to actively modulate the SSIII [ 10 , 107 , 116 ].…”
Section: Regulation Of Starch Phosphorylasementioning
confidence: 99%